Differential effects of fertilisers on pollination and parasitoid interaction networks. Issue 2 (28th October 2020) - Villa‐Galaviz, Edith; Smart, Simon M.; Clare, Elizabeth L.; Ward, Susan E.; Memmott, Jane
Abstract: Grassland fertilisation drives non‐random plant loss resulting in areas dominated by perennial grass species. How these changes cascade through linked trophic levels, however, is not well understood. We studied how grassland fertilisation propagates change through the plant assemblage into the plant–flower‐visitor, plant–leaf miner and leaf miner–parasitoid networks using a year's data collection from a long‐term grassland fertiliser application experiment. Our experiment had three fertiliser treatments each applied to replicate plots 15 m 2 in size: mineral fertiliser, farmyard manure, and mineral fertiliser and farmyard manure combined, along with a control of no fertiliser. The combined treatment had the most significant impact, and both plant species richness and floral abundance decreased with the addition of fertiliser. While insect species richness was unaffected by fertiliser treatment, fertilised plots had a significantly higher abundance of leaf miners and parasitoids and a significantly lower abundance of bumblebees. The plant–flower‐visitor and plant–herbivore networks showed higher values of vulnerability and lower modularity with fertiliser addition, while leaf miner–parasitoid networks showed a rise in generality. The different groups of insects were impacted by fertilisers to varying degrees: while the effect on abundance was the highest for leaf miners, the vulnerability and modularity of flower‐visitor networks was the most affected. The impact on the abundance of leaf miners was positive and three times higher than the impact on parasitoids, and the impact on bumblebee abundance was negative and double the magnitude of impact on flower abundance. Overall, our results show that while insect species richness was unaffected by fertilisers, network structure changed significantly as the replacement of forbs by grasses resulted in changes in relative abundance across trophic levels, with the direction of change depending on the type of network. Synthesis . By studying multiple networks simultaneously, we were able to rank the relative impact of habitat change on the different groups of species within the community. This provided a more holistic picture of the impact of agricultural intensification and provides useful information when deciding on priorities for mitigation. Abstract : The authors showed – for the first time – the relative effect of fertilisers on three different ecological networks simultaneously, in a long‐term experiment. They observed that flower visitors are far more affected than parasitoids, these effects being mediated by changes in the plant community.